Exact mind : an artist with asperger syndrome - Baron-Cohen, Simon (Jessica Kingsley, 2004)
Peter Myers's intricate and ornately patterned drawings are brought together for the first time in this volume, which is the fascinating result of the collaboration of an artist and two scientists. The beautiful, complex images (included in full-page colour as well as black and white reproductions) serve as a rare window into the precision and creativity of the Asperger mind at work. Peter Myers was diagnosed with Asperger Syndrome in 1996 and his work reflects his stunning ability to plan and to organize visual information, and to embed illusions within his pictures. In explanatory text along.